Pengaruh Perasan Daun Kamboja (Plumeria acuminata) Terhadap Kematian Lalat Rumah (Musca domestica) - Rosida; Dewi Puji Lestari; Amaliyah Nurul Hidayah; Hadi Barru H.F.S (FMIPA : Universitas PGRI Adi Buana, 2022)
Flies are insects that act as vectors of mechanical disease, because disease agents such as pathogenic bacteria do not change in the fly's body but only move disease agents from polluted places to clean places. Flies can be controlled with plant-based insecticides. The purpose of this study was to determine the effect of frangipani leaf juice (Plumeria acuminata) on the death of house fly (Musca domestica). This research is an experimental research with the design of